2017
DOI: 10.1292/jvms.16-0061
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations of adipokines in goat milk: relation to plasma levels, inflammatory status, milk quality and composition

Abstract: The main objectives of our study were to measure the major adipokines adiponectin, leptin and resistin in goat milk, to assess their interrelationships and to assess their relationships with the plasma and serum concentrations of total protein, cholesterol, total lipids, plasma C-reactive protein (CRP), milk somatic cell count (SCC), milk total aerobic colony and lactobacillus count, and milk components in lactating Saanen goats. The study was performed on eighteen lactating Saanen goats. Milk and blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(60 reference statements)
0
2
0
1
Order By: Relevance
“…The putative role of milk adiponectin remains to be determined. However, the inverse correlation between somatic cell count and adiponectin concentrations in goat milk suggests a role for adiponectin in udder health (Guzel et al, 2017). The observation that adiponectin-deficient mice have reduced intestinal epithelial cell differentiation (Saxena et al, 2013) and the presence of adiponectin receptors in the intestine of human (Yoneda et al, 2008) and mouse embryos (Zhou et al, 2005) further suggest a role for adiponectin in neonatal intestinal maturation.…”
Section: Milk Adiponectin and Its Biological Significance In The Neonatementioning
confidence: 99%
See 1 more Smart Citation
“…The putative role of milk adiponectin remains to be determined. However, the inverse correlation between somatic cell count and adiponectin concentrations in goat milk suggests a role for adiponectin in udder health (Guzel et al, 2017). The observation that adiponectin-deficient mice have reduced intestinal epithelial cell differentiation (Saxena et al, 2013) and the presence of adiponectin receptors in the intestine of human (Yoneda et al, 2008) and mouse embryos (Zhou et al, 2005) further suggest a role for adiponectin in neonatal intestinal maturation.…”
Section: Milk Adiponectin and Its Biological Significance In The Neonatementioning
confidence: 99%
“…Some adipokines known to be important regulators of energy metabolism, food intake, and insulin sensitivity were found in human milk (Çatlı et al, 2014). Among these, apelin, ghrelin, and resistin were detected in the colostrum and milk of farm animals (Rosi and Rapetti, 2004;Mesmin et al, 2011;Woliński et al, 2014;Guzel et al, 2017), but their potential role in neonatal growth and health has never been investigated. In a recent paper, Suzuki et al (2015) reported that chemerin transcripts were not detected in MAC-T cells and weak transcript levels were observed in the bovine mammary gland, probably due to the presence of embedded adipocytes.…”
Section: Other Adipokinesmentioning
confidence: 99%
“…A leptina é o hormônio associado com a regulação da saciedade, da taxa metabólica basal, massa corporal e gasto energético (Guzel et al, 2017), sintetizada principalmente no tecido adiposo. Dessa maneira, pode-se observar que os níveis aumentam de forma proporcional ao aumento de massa gorda; sendo assim, em pessoas obesas, podemos observar um nível elevado de leptina (Mehrdad et al, 2020).…”
Section: Introductionunclassified